2022
DOI: 10.34067/kid.0000422021
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Endotrophin Are Prognostic for Long-Term Mortality after AKI

Abstract: Background: Acute kidney injury (AKI) is a rapid decrease in kidney function that may be associated with structural damage. Early markers predicting AKI are emerging, but tools to assess patients' long-term health risks after AKI are still lacking. Endotrophin (ETP) is a bioactive molecule released during formation of collagen type VI. We evaluated the potential of circulating ETP as a prognostic biomarker of adverse outcome following AKI. Methods: We measured ETP in plasma samples collected 1 year after an ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Other studies revealed that adhesive glycoprotein fibronectin (FN) is also found [202][203][204]. Our group recently showed that circulating endotrophin, a collagen VI precursor, was involved in the pathogenesis and was a prognostic for mortality after AKI [205]; it was also involved in the development of fibrosis following IgA nephritis and ANCA vasculitis [206].…”
Section: Fibrosis In Ckdmentioning
confidence: 99%
“…Other studies revealed that adhesive glycoprotein fibronectin (FN) is also found [202][203][204]. Our group recently showed that circulating endotrophin, a collagen VI precursor, was involved in the pathogenesis and was a prognostic for mortality after AKI [205]; it was also involved in the development of fibrosis following IgA nephritis and ANCA vasculitis [206].…”
Section: Fibrosis In Ckdmentioning
confidence: 99%
“…NAD molecules and their activity in electron transfer in renal tissue has been shown to be low in CKD states. These cascade of oxidative in ammatory cells markers have been shown to contribute to renal brosis (19)(20)(21). Mitochondrial dysfunction has also been observed in CKD, and preventing mitochondrial damage reduces brogenesis in rat models (22).…”
Section: Introductionmentioning
confidence: 99%